ANALISIS PENGARUH CAPITAL ADEQUACY RATIO, LOAN TO DEPOSIT RATIO, NON PERFORMING LOAN, LEVERAGE MULTIPLIER, LOAN TO ASSETS RATIO, EQUITY TO TOTAL ASSETS RATIO TERHADAP PROFITABILITAS PERBANKAN (Studi Kasus Pada Bank Umum Konvensional yang Terdaftar di BEI Periode Tahun 2012-2016) - Diana Sulistiyaningrum, 14.05.52.0205; Lisiantara, G. Anggana (Students' Journal of Accounting and Banking, 2018)
This study aims to examine the impact of Capital Adequacy Ratio, Loan to Deposit Ratio, Non Performing Loans, Leverage Multiplier, Loan to Assets Ratio, Equity to Total Assets Ratio Toward Banking Profitability (In Conventional Commercial Banks Listed on BEI in the Year of 2012-2016). Besides, the measurement of bank profitability used was Return On Assets. Moreover, sampling method used was purposive sampling with period of research in the year of 2012 until 2016 and obtained by 21 banking company. The relationship and / or the impact between variables was explained by using analysis method of panel data regression using Eviews 9.0 program. The result of the research showed that CAR had no significant effect to ROA, LDR had significant positive effect to ROA, then NPL and LAR had significant negative effect to ROA, and LM and EAR had no significant negative effect to ROA.Keywords: Financial Ratio, Profitability, Conventional